Улаанбаатар Орчмын “Сонгино” Идэвхитэй Хагарал Дээрхи Георадарын Судалгааны Анхан Шатны Үр Дүнгээс - Ц, Нямбаяр; Bano, Maksim; Schlupp, Antoine; M, Өлзийбат; Д, Баттогтох; Э, Баярсайхан; Г, Баатарсүрэн; Б, Бямбахорол (Scientific transaction of the National University of Mongolia. Physics, 2022)
The seismic activity observed in the vicinity of Ulaanbaatar (UB) city not only has been increased since 2005, but it is also organized, at least, on two perpendicular directions which determine two active faults: Emeelt fault (40 km long, situated 15 km NW of UB) and Hustai fault (80 km long, less than 30 km West of UB). The Songino fault (10 km long, situated 20 km West of UB) is located between Emeelt and Hustai fault. Their length and morphology indicate they can produce earthquakes of magnitude 6.5 to 7.5. Most of the Mongolian population (1.5 million over 3 million) is concentrated around UB city which is the main political and economical centre of the country. Hence, the study of seismic hazard is of first importance for the country. Since the last large earthquake, the fault geomorphology has been smoothed due to erosion processes and a low slip rate. The exact location of the fault is thus hidden in a several meter strip. In such a context, the Ground Penetrating Radar (GPR) method gives good and useful results and can help to characterize faults by identifying offsets of radar reflectionsand buried fluvial channel deposits. In order to image and characterize these faults, we have conducted many GPR campaigns in 2010, 2012 and 2013 over active areas around UB. In our study we present only some preliminary results of GPR measurements performed along the Songino fault (in 2013). The objective is to understand its geometry (dip, length, orientation) and the type of displacements and amplitude. In this survey we used 250 MHz, 500 MHz shielded antenna and RTA 50 MHz unshielded antenna and also used a differential GPS in order to measure the topography. One trench has been dug in Songino area.